Reliability and Relationship to Retention of Assessing an Acquisition Rate for Sight Words With Kindergarten Students. (December 2018) - Taylor, Crystal N.; Aguilar, Lisa; Burns, Matthew K.; Preast, June L.; Warmbold-Brann, Kristy
Teaching children too many words during a lesson reduces retention. The amount of new information a student can successfully rehearse and recall later is called acquisition rate (AR), which has been reliably measured with students in first, third, and fifth grades. The purpose of this study was to examine the reliability of assessing AR for sight words with kindergarten students. A total of 32 kindergarten students from five classrooms across two elementary schools participated in the study. AR was measured twice over a 2-week period, and 1-day retention was measured for the first AR. The AR data resulted in a 2-week delayed alternate form reliability of r = .83, and there was also a strong correlation between AR and number of words retained 1 day later. The limitations, implications, and considerations for the name of the construct being assessed are discussed.